Plumbagin Inhibits Proliferation, Migration, and Invasion of Retinal Pigment Epithelial Cells Induced by FGF-2. (October 2021) - Zhang, Yang; Wang, Ri; Zhang, He; Liu, Liya; An, Jianbin; Hao, Jun; Ma, Jingxue
Highlights: Plumbagin inhibited FGF-2-induced proliferation, migration, and invasion of RPE cells. Plumbagin suppressed the protein expression of MMP-2/-9, Col1A1, Col4A1, and Col6A1 of RPE cells. Plumbagin inhibited FGFR1, FGFR2 phosphorylation. Plumbagin inhibited activation of downstream MAPK signaling pathway. Plumbagin may be a potential drug for prevention of PVR due to its inhibitory effect. Abstract: Proliferative vitreoretinopathy (PVR) is a serious ophthalmic disease and characterized by the formation of proliferative membranes by retinal pigment epithelial (RPE) cells. In PVR, the contraction and traction of the fibrocellular membranes cause retinal detachment, which can cause reduction surgery for retinal detachment to fail. Fibroblast growth factor-2 (FGF-2) causes RPE cells to form extracellular matrix (ECM), promotes chemotaxis, mitosis, and positively promotes the disease process of PVR. Plumbagin (PLB) is a plant small molecule naphthoquinone compound. It has the functions in anti-tumor, anti-inflammatory, inhibit proliferation. We tried to investigate the possible effects of PLB on the biological behavior of ARPE-19 cells induced by FGF-2 and its underlying mechanisms. Our study confirmed that proliferation, migration, and invasion of ARPE-19 cells induced by FGF-2 (10 ng/ml) were significantly inhibited by PLB. PLB also significantly inhibits the expression of MMP-2/-9, collagen I Alpha 1 (Col1A1), collagen IV Alpha 1 (Col4A1), collagen VI Alpha 1 (Col6A1), and the phosphorylation of FGF receptor (FGFR)-1, FGFR-2, ERK, p38, JNK of FGF-2-induced ARPE-19 cells. In summary, PLB inhibits FGF-2-stimulated proliferation, migration, and invasion of ARPE-19 cells, which may take place through inhibiting the expression of MMP-2/-9, Col1A1, Col4A1, Col6A1, and the mitogen-activated protein kinase (MAPK) pathway. PLB may have a preventive effect on proliferation, migration, and invasion of FGF-2-induced ARPE-19 cells.